Changes in the geometry and strength of the Atlantic meridional overturning circulation during the last glacial (20-50 ka) - Burckel, Pierre; Waelbroeck, Claire; Luo, Yiming; Roche, Didier M.; Pichat, Sylvain; Jaccard, Samuel L.; Gherardi, Jeanne; Govin, Aline; Lippold, Jörg; Thil, François (Climate of the past, 2016)
We reconstruct the geometry and strength of the Atlantic meridional overturning circulation during the Heinrich stadial 2 and three Greenland interstadials of the 20-50 ka period based on the comparison of new and published sedimentary 231Pa / 230Th data with simulated sedimentary 231Pa / 230Th. We show that the deep Atlantic circulation during these interstadials was very different from that of the Holocene. Northern-sourced waters likely circulated above 2500 m depth, with a flow rate lower than that of the present-day North Atlantic deep water (NADW). Southern-sourced deep waters most probably flowed northwards below 4000 m depth into the North Atlantic basin and then southwards as a return flow between 2500 and 4000 m depth. The flow rate of this southern-sourced deep water was likely larger than that of the modern Antarctic bottom water (AABW). Our results further show that during Heinrich stadial 2, the deep Atlantic was probably directly affected by a southern-sourced water mass below 2500 m depth, while a slow, southward-flowing water mass originating from the North Atlantic likely influenced depths between 1500 and 2500 m down to the equator.